PENGUJIAN PENGERING TENAGA SURYA TIPE PEMANASAN LANGSUNG UNTUK PENGERINGAN PISANG PADA KONDISI BERBEDA - Azridjal Aziz; Ahmad Surya; Rahmat Iman Mainil (Jurnal Sains dan Teknologi, 2019)
The direct solar dryer has been tested for drying bananas under different conditions. The dryer being tested is a hybriddryer that can be used with other energy sources, in addition to using solar energy as the main energy source during theday, while LPG gas is used for drying at night. The results showed that the highest temperature, the highest decrease inwater content in the test with LPG was obtained on shelf 6, while the lowest was obtained on shelf 1, because the heatsource was at the bottom of the dryer on shelf 6, the opposite happened to dry using solar energy because the heat sourcecame from the top of the shelf 1. In testing with LPG, the highest temperature that can be achieved is 84.7 ° C, on shelf6, while the lowest temperature is 52.3 ° C on shelf 1, on the other hand, the temperature of bananas using solar poweris the highest temperature on the shelf 1 at 11.00 WIB at 62.9 ° C and the lowest on shelf 1 at 17.00 WIB at 37.1 ° C. Thetotal energy requirement for drying in the test using LPG was 4681.92 kJ, while the total energy requirement for dryingin the test using solar power was 3176.24 kJ. Drying using solar energy is more economical than using LPG gas, but thedrying time is longer than LPG. Drying using a dryer technology have better quality and hygienic than open sun drying.